2004
DOI: 10.1097/01.coc.0000092597.31938.51
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Postexcision Preradiation Mammography in Patients With Early-Stage Breast Cancer

Abstract: The purpose of this study was to evaluate the benefit of postexcision preradiation mammography for patients with early-stage breast cancer. The records of 101 patients (103 breasts) with either ductal carcinoma in situ (DCIS) or early invasive breast cancer diagnosed based on microcalcifications on a mammogram between January 1999 and December 2001 at our institution were reviewed. Sixty-one patients had a postexcision preradiation mammogram, and 42 patients did not have a mammogram until the completion of rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…To our knowledge this is the largest study evaluating locoregional restaging after BCS and chemotherapy by mammogram and its impact on the waiting time for radiotherapy. A few studies evaluated the use of preradiotherapy mammograms in patients presenting presurgical suspicious calcifications 4,5 . A previous study conducted by Teixidor et al 6 investigated the value of mammography after BCS before radiotherapy including 120 patients with breast cancer regardless of the presence or absence of microcalcifications on their diagnostic mammograms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge this is the largest study evaluating locoregional restaging after BCS and chemotherapy by mammogram and its impact on the waiting time for radiotherapy. A few studies evaluated the use of preradiotherapy mammograms in patients presenting presurgical suspicious calcifications 4,5 . A previous study conducted by Teixidor et al 6 investigated the value of mammography after BCS before radiotherapy including 120 patients with breast cancer regardless of the presence or absence of microcalcifications on their diagnostic mammograms.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no universal agreement about the utility of preradiotherapy mammograms. Previous studies have focused on the role of preradiotherapy mammograms in patients with a preoperative mammogram with suspicious microcalcifications leading to the diagnosis of breast cancer 4,5 . These studies supported the use of postexcision preradiotherapy mammogram if preexcision microcalcifications were present, with the highest positive predictive value being found in patients with ductal in situ carcinomas 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Second, the rates of residual suspicious calcifications on post-excision mammography and residual malignancy in our study was higher than those previously reported. 12,25,26 However, excisions were performed in our study for pathologic confirmation and not for complete tumor removal.…”
Section: Gyeongmin Park Et Almentioning
confidence: 99%
“…Mammography may be able to establish a baseline for radiologic follow-up but whether it helps to determine the adequacy of tumor excision is controversial. [12][13][14][15][16] Diagnostic assessment of the postoperative breast is often challenging because inflammatory changes may be vague or mimic malignancy. 14,17,18 However, to perform a complete excision, it is important to accurately predict residual malignancy after excisional biopsy if suspicious microcalcifications are present.…”
Section: Introductionmentioning
confidence: 99%
“…Postexcision preirradiation mammograms (PPMs) performed within a short time period after breast‐conserving surgery, but prior to adjuvant radiation, can be utilized to identify any radiographic evidence of residual disease. Previous attempts to ascertain the clinical benefit from a PPM have been hindered by small sample sizes and selection bias and have been retrospective in nature . Because only women considered to have a high risk of residual disease had postlumpectomy mammograms orders, many series likely overestimate the frequency of residual suspicious calcifications on PPM.…”
Section: Introductionmentioning
confidence: 99%